PERBANDINGAN KONSEP KEKUASAAN DAN MODEL SISTEM POLITIK INTERNASIONAL ANTARA PERSPEKTIF REALIS DENGAN ISLAM - Amri Hakim (Dauliyah Journal of Islamic and International Affairs, 2016)
The objectives of this study are to explore Islamic Idea about the concept of power and model of the international political system as Realist central theme, in order to guide Moslem International Relations Scholar knowing the meaning of their existence as Allah servant. This study also as the first step to constructing the practice of international relations based on Islamic Idea. The method of this study is “the revelation guide science” by interpreted Al Quran and Hadist, dialectic it with the mainstream theories and the reality of international relations, and then from the propositions of Islamic Idea, which are: power is the central concept of Islam Religion. Allah is the owner of absolute power on the universe. Human in every level of the social institution has the relative power. Human relative power is limited by space, time and relational. Human relative power comes from Allah as His delegation on the earth. The sources of human relative power are Wisdom, strength, wealth, and beautiful. Every human being who hold the relative power role as Allah agent for the merciful of the universe. The relative power will be audited by Allah S.W.T. The model of the international political system in Islamic Idea is World Society.